RESPONSIVENESS OF THE TRANSPORTATION AGENCY IN THE SERVICE OF PUBLIC STREET LIGHTING IN PEKANBARU CITY - Nadila Saumitri; Geovani Meiwanda (FISIP Universitas Malikussaleh, 2022)
One of the road equipment that must be installed is public street lighting. In its implementation, lighting for public roads must be managed properly by those who have the authority to manage it. In this research, the Pekanbaru City Transportation Service is an agency that has duties and functions in providing Public Street Lighting (PJU) services in Pekanbaru City. In the implementation of this public street lighting service, several obstacles are often encountered for the Pekanbaru City Transportation Service. This study looks at the responsiveness of the Pekanbaru City Transportation Service in providing lighting services for public roads, as well as the variables that hinder the Pekanbaru City Transportation Service's ability to respond to issues regarding lighting for public roads in Pekanbaru City. The researcher saw the responsiveness of the Pekanbaru City Transportation Service with the Responsiveness indicator by Agus Dwiyanto. By using a qualitative research method approach and a descriptive approach to conduct research related to this situation. Research findings about the responsiveness of the Department of Transportation in public street lighting services in Pekanbaru City are still not optimal. Then there are several obstacles in the implementation of public street lighting services in Pekanbaru City. Salah satu perlengkapan jalan yang harus dipasang adalah penerangan jalan umum. Dalam penyelenggaraannya, Penerangan untuk jalan umum wajib dikelola dengan baik oleh pihak yang memiliki kewenangan dalam mengelolanya. Dalam penelitian ini, Dinas Perhubungan Kota Pekanbaru menjadi instansi yang memiliki tugas dan fungsi dalam menyelenggarakan pelayanan Penerangan Jalan Umum (PJU) di Kota Pekanbaru. Dalam penyelenggaraan pelayanan penerangan jalan umum ini masih kerap ditemui beberapa kendala bagi Dinas Perhubungan Kota Pekanbaru. Penelitian ini melihat ketanggapan Dinas Perhubungan Kota Pekanbaru dalam memberikan pelayanan penerangan untuk jalan umum, serta variabel-variabel yang menghambat kemampuan Dinas Perhubungan Kota Pekanbaru dalam menanggapi persoalan mengenai penerangan untuk jalan umum di Kota Pekanbaru. Peneliti melihat responsivitas dari Dinas Perhubungan Kota Pekanbaru dengan indikator Responsivitas oleh Agus Dwiyanto. Dengan menggunakan pendekatan metode penelitian kualitatif dan pendekatan deskriptif melakukan penelitian terkait situasi ini. Temuan pen elitian tentang ketanggapan Dinas Perhubungan dalam pelayanan penerangan jalan umum di Kota Pekanbaru masih belum optimal. Kemudian terdapat beberapa kendala dalam pelaksanaan pelayanan penerangan jalan umum di Kota Pekanbaru.